Factors influencing the use of privacy settings in location-based social networks - Oladimeji, Henry (Department of Information Systems, 2018)
The growth of location-based social networks (LBSN) such as Facebook and Twitter has been rapid in recent years. In LBSNs, users provide location information on public profiles that potentially can be used in harmful ways. LBSNs have privacy settings that allow users to control the privacy level of their profiles, thus limiting access to location information by other users; but for various reasons users seldom make use of them. Using the protection motivation theory (PMT) as a theoretical lens, this dissertation examines whether users can be encouraged to use LBSN privacy settings through fear appeals. Fear appeals have been used in various studies to arouse fear in users, in order to motivate them to comply to an adaptive behaviour through the threat of impending danger. However, within the context of social networking, it is not yet clear how fear-inducing arguments will ultimately influence the use of privacy settings by users. The purpose of this study is to investigate the influence of fear appeals on user compliance, with recommendations to enact the use of privacy settings toward the alleviation of privacy threats. Using a survey methodology, 248 social-network users completed an instrument measuring the variables conceptualized by PMT. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the validity and reliability, and to analyze the data. Analysis of the responses show that PMT provides an explanation for the intention to use privacy settings by social-network users. Risk susceptibility, response efficacy, self-efficacy and response cost were found to have a positive impact on the intention to use privacy settings, while sharing benefits and maladaptive behaviours were found to have a negative impact on the intention to use privacy settings. However, risk severity and fear were not found to be significant predictors of the intention to use privacy settings. This study contributes to existing research on PMT in a sense that fear appeal should focus more on coping appraisal, rather than on threat appraisal which is consistent with the results of most studies on protection motivation.